Pembangunan Taman Wisata Eko-Kuliner di Daerah Aliran Sungai Badung untuk Mendukung Pariwisata Budaya di Kota Denpasar - Purnaya, I Gusti Ketut; Supartini, Ni Luh; Trisna Semara, I Made (Jurnal Kajian Bali (Journal of Bali Studies); Vol 9 No 1 (2019): WACANA KRITIS BUDAYA BALIDO - 10.24843/JKB.2019.v09.i01.p04, 2019)
The river has a substantial contribution in our life. But in reality the quality of rivers in Indonesia is in a heavily polluted condition. Various river structuring efforts have been carried out such as maintaining cleanliness, managing the smooth running of water, and educating people not to throw garbage into the river. This article aims to identify potential and determine the design in developing the Badung River basin to support the development of cultural tourism in Denpasar City. The technique of collecting data uses non-participant observation, document study, and in-depth interviews. This article concludes that Sungai Badung has a variety of tourism potential that can be developed as a new tourist attraction. The concept of development by designing eco-culinary tourism parks combines the concepts of ‘eco-tourism’ and ‘culinary tourism’ in an effort to create sustainable tourism without damaging the river ecosystem.